Techno-Economic Assessment of Rice Seedling-Raising Trays in Northern Iran - Allameh, Alireza (New Countryside, 2025)
Mechanized rice transplanting has become an essential practice in modern rice cultivation due to its economic advantages, reduced labor requirements, and shorter operation time compared with manual transplanting. However, successful mechanized transplanting depends on the provision of high-quality mat-type seedlings, which are produced in specially designed plastic trays. These trays play a critical role in seedling establishment and ultimately influence crop performance. In this study, nine types of rice seedling-raising trays were evaluated—four made from high-quality virgin materials and five from recycled plastics—to assess their effects on seedling mat quality, transplanting efficiency, yield, and yield components. The experiment was conducted using a Randomized Complete Block Design (RCBD) with three replications. Results showed that seedling mats raised in high-quality trays (P10, PK, P50, and RF) exhibited significantly better performance (p < 0.05) compared to those raised in recycled trays. Seedlings grown in quality trays had greater shoot cross-sectional area and higher strength, resulting in improved mechanical transplanting efficiency. Key transplanting traits—including the number of hills per unit area, hill spacing uniformity, number of seedlings per hill, and rates of missing, buried, or damaged seedlings—were all significantly superior in the quality tray treatments. Similarly, grain yield and yield components were significantly higher for seedlings raised in quality trays, which also demonstrated greater resistance to lodging. In contrast, recycled trays exhibited substantial deformation (bulging, twisting, and breakage) due to weak polymer bonding, leading to poor mat uniformity. The economic analysis confirmed that, despite their higher purchase price, using quality trays was economically justified, with a production cost of approximately 0.23 USD per kilogram of paddy, compared with 0.29 USD for recycled trays